FACTORS AFFECTING ENTREPRENEURS DECISION ON USE SHIPPING AGENT IN SAMUT PRAKAN PROVINCE - Saengpray, Thanyarat; Visitnitikitja, Chinnaso (Journal of MCU Nakhondhat, 2023)
This study aimed to investigate and analyze several key aspects, including 1) Marketing Mix Factors on use shipping agent in Samut Prakan province. 2) Decision-Making on use shipping agent in Samut Prakan province. 3) Comparative Decision-Making on use shipping agent in Samut Prakan province based on establishment information 4) The impact of Marketing Mix Factors on the decision to engage a shipping agent in Samut Prakan province. The study focused on individuals employed in import-related businesses and the Customs clearance process within Samut Prakan Province, Thailand. A total of 400 participants were surveyed using a questionnaire as the primary research instrument. Data analysis included percentage calculations, mean values, t-tests, F-tests (One-way ANOVA), and Multiple Regression Analysis. The results indicated that, on average, respondents had a significantly favorable opinion regarding marketing mix factors. Additionally, respondents generally strongly agreed with decision-making processes. Interestingly, the research found that differences in establishment information did not significantly influence the decision to engage a shipping agent in Samut Prakan Province. However, factors related to Product Process/Services and Physical Evidence exhibited a statistically significant impact at the .05 significance level. This conclusion discussion and finding for the entrepreneurs, indicates that should be emphasizing the importance of customs clearance process by systematically and accurately, Storage safety management. And create cooperate image to be know and valuable includes manpower and business development to be expert and professional with customs service efficiency to be the one and the first choice for customer decision on use shipping agent.